Analisis Determinan Faktor-Faktor yang Mempengaruhi Opini Audit Going Concern pada Perusahaan-Perusahaan di Sektor Energi yang Listing di Bursa Efek Indonesia - Loupatty, Linda; Usmany, Paul (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research aims to empirically test the factors that influence the Going Concern Audit opinion. The determining factors that influence the Going Concern Audit Opinion in this research are leverage, company size, institutional ownership and managerial ownership. Research was conducted on companies in the Energy sector listed on the Indonesian Stock Exchange in 2019-2022. The sample used was 10 companies with observations for 4 years, so the total number of observations was 40. This research data uses secondary data, namely annual reports of companies in the energy sector listed on the Indonesia Stock Exchange for 2019-2022. Data were analyzed using Logistic Regression Analysis. The results of this research show that leverage has a positive and significant effect on going concern audit opinion, company size has no effect on going concern audit opinion, institutional ownership has a positive and significant effect on going concern audit opinion, managerial ownership has a positive and significant effect on going concern audit opinion.